Innovation as a policy strategy for natural resource protection. (16th July 2019) - Peterson, Jeffrey M.
Abstract: Growing global food demands place major strains on water resources, including quality impairments and increased water scarcity. Drawing on the largely separate bodies of literature on externalities and technological innovation, this article develops a dynamic framework to explore the long‐term impacts of alternative policy approaches to the agricultural impacts on water resources. Environmental policies, which focus on correcting environmental externalities, lead to an overall gain because costs to farmers are more than offset by reduced environmental damages. Technology policies, which direct public investments into agricultural eco‐innovations, lead to benefits for farmers as well as the environment. Joint implementation of both types of policies leads to the largest overall gain. In principle, a technology policy alone could have greater environmental benefits than an environmental policy alone. This outcome is most likely in cases where the productivity effect of new technology is large and the cost of research is low. Recommendations for research managers As an alternative to traditional environmental policy, investments in research can provide win–win solutions that benefit the environment and agricultural producers. Conceivably, eco‐innovations could lead to environmental conditions that are better than those achieved by environmental policy alone. Adding research investments to existing environmental policy would lead to further improvements in environmental quality while also benefitting farmers. Unlike environmental policies that are perceived to impose costs on agriculture, technology policies impart benefits to farmers and are less likely to face political opposition from industry. Technology policies are likely to be the most effective when eco‐innovation leads to technologies that meaningfully reduce environmental impacts and also raise farm productivity.